ANALISIS PENGARUH VARIASI ARUS PENGELASAN TERHADAP KEKUATAN TARIK DAN STRUKTUR MIKRO PADA SAMBUNGAN LAS SMAW DAN FCAW DENGAN MATERIAL BAJA KARBON RENDAH - Picanussa, Jovancko. S. S.; Nanulaitta, Nevada. JM; Huka, Graciadiana I (Journal Mechanical Engineering, 2024)
Carbon steel is a type of alloy steel consisting of various elements, especially iron (Fe) and carbon (C). In general, the properties of steel are influenced by the percentage of carbon and the microstructure of the steel which is influenced by the composition of the steel and heat treatment. The welding process can change the structure and composition of the steel. In this study, the welding process used is SMAW and FCAW welding. Then the testing process is carried out, namely tensile testing and microstructure to see the effect of variations in the welding current used. In this study, the author will analyze the effect of variations in welding current on tensile strength or mechanical properties as well as the structure and composition of the specimen to be tested in this case medium carbon steel. The welding methods used are FCAW (Flux Core Arc Welding) and SMAW (Shield Metal Arc Welding). The results of this study, the author found that the welding current has an effect on the tensile strength and microstructure of medium carbon steel. Where for tensile strength, the greater the welding current used, the greater the tensile strength of the specimen where the current range used must be adjusted to the thickness of the workpiece used. In FCAW 90A the value obtained is 438.30 MPa and the strain value is 6.20% and SMAW 90A the value obtained is 438.20 MPa and the strain is 7.20%. Likewise, the Pmax and ΔL values where in SMAW 90 ampere the Pmax value is 43.82 KN and ΔL 3.60mm, FCAW 90 ampere the Pmax value is 43.83 KN and ΔL 3.10mm. With this, the author concludes that with a material thickness of 8mm and a current variation of 70 amperes and 90 amperes, it was found that at a larger welding current of 90 amperes, the tensile strength obtained was greater and for the microstructure, the author found changes in the structure of the welding results in FCAW welding where in the raw material the structure found was ferrite and pearlite while for the FCAW welding results, a beanite structure was found. Keywords: Welding, tensile strength, microstructure.